SURVEI KEMAMPUAN SERVIS DALAM PERMAINAN BOLA VOLI KLUB TANGGO RAJO - Gian Rahmat Sahasra; M Iqbal Al Ihsan; Ikhsan Maulana Putra; Titis Wulandari (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Abstract This research was motivated by not knowing whether the service technique used was correct or not, and not knowing the player's level of ability regarding basic volleyball techniques. This study aims to determine the level of upper serve and lower serve abilities of volleyball players at the Tanggo Rajo club, Kab. Tebo. This research uses quantitative descriptive methods. The population is all volleyball players at the Tanggo Rajo club, Kab. Tebo, numbering 15 people. The sampling technique used total sampling with a research sample of 15 players. Data collection techniques using tests. The instrument used is the American Association for Health, Physical Education, and Recreation (AAHPER) serving accuracy test. The analysis technique used is to put the frequency into percentage form. The results of this research indicate that the level of service ability of volleyball players at Tanggo Rajo Club, Kab. Tebo is sufficient considering the highest frequency, namely the sufficient category with 7 people, namely 47%. Level of service ability of Tanggo Rajo Club volleyball players, Kab. Tebo was categorized as very good at 13%, good at 13%, fair at 47%, poor at 20%, very poor at 7%. Meanwhile, the lower level of service ability of the Tanggo Rajo Club volleyball players, Kab. Tebo is sufficient considering the highest frequency, namely the sufficient category with 6 people, namely 40%. Level of lower service ability of Tanggo Rajo Club volleyball players, Kab. Tebo was categorized as very good at 7%, good at 20%, fair at 40%, poor at 33%, very poor at 0%.. Keywords : Ability, Upper Serve, Lower Serve